A porous ceramic atomizing core and a method for manufacturing the same

CN122916636APending Publication Date: 2026-10-16ALD GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611000743.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

本申请的技术目的在于提供一种多孔陶瓷雾化芯及其制备方法,旨在解决相关技术中雾化芯的金属发热技术路线在加热时容易氧化产生灰分、或与烟油成分反应生成潜在有害物质;还可能会与基体剥离脱落;以及产生焦糊味的技术问题

Benefits of technology

[0015] Compared with related technologies, the porous ceramic atomizing core and its preparation method in this application have the following advantages: This application uses conductive ceramic to replace metal as the heating path of the porous ceramic atomizing core, and adds potassium hexatite whiskers to the porous ceramic matrix and heating slurry for reinforcement, significantly improving the strength of the porous ceramic atomizing core and extending its service life. The atomizing core has strong oxidation resistance and no risk of volatiles or metal precipitation; the heating path reinforced by potassium hexatite whiskers has a high degree of matching with the thermal expansion coefficient of the matrix, significantly improving the bonding force, approaching integration, and significantly improving the resistance to thermal fatigue; it has high resistance stability, no burnt or off-flavor, and greatly improves the consistency of taste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916636A_ABST
    Figure CN122916636A_ABST
Patent Text Reader

Abstract

The application provides a porous ceramic atomizing core and a preparation method thereof. The preparation method comprises the following steps: obtaining non-conductive ceramic powder, potassium hexatitanate whiskers, sintering aids, pore-forming agents, binders and a first solvent; then, after ball milling, granulation, molding and sintering, a porous ceramic matrix is prepared; obtaining conductive ceramic powder, potassium hexatitanate whiskers, sintering aids, pore-forming agents, binders and a second solvent; then, after dispersion and slurry preparation, a heating slurry is obtained; the heating slurry prepared in step 2 is printed on the surface of the porous ceramic matrix prepared in step 1, so as to form a heating path on the porous ceramic matrix; and the porous ceramic matrix printed with the heating slurry is sintered, thereby obtaining the porous ceramic atomizing core. In the application, the conductive ceramic is used to replace metal as the heating path of the porous ceramic atomizing core, and the potassium hexatitanate whiskers are added to the porous ceramic matrix and the heating slurry to strengthen the porous ceramic atomizing core, so that the strength of the porous ceramic atomizing core is improved and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of electronic atomization technology, and in particular relates to a porous ceramic atomizing core and its preparation method. Background Technology

[0002] Porous ceramic atomizing cores have a rich pore structure, which can store and transport liquids. Moreover, compared with organic / inorganic cotton cores, porous ceramics also have the characteristics of high temperature resistance, stable atomization, and long service life, and are widely used in atomizers.

[0003] In related technologies, porous ceramic atomizing cores include metal heating circuits and porous ceramic substrates. The metal heating circuits can be metal heating wires, made of materials such as iron-chromium alloys, iron-chromium-aluminum alloys, and 306 stainless steel; they can also be a slurry composed of metal powder and sintering aids, printed into specific patterns using a thick-film process and sintered to form conductive circuits. The porous ceramic substrate is generally composed of diatomaceous earth, quartz, alumina, or zirconium oxide. While current porous ceramic atomizing cores can effectively heat and atomize e-liquid, providing a better vaping experience, the heating process still relies on metal conducting electricity to atomize the e-liquid. However, metal is prone to oxidation under heat, producing ash, or reacting with e-liquid components to generate potentially harmful substances, all of which could pose health and safety risks to users. Furthermore, the mismatch in thermal expansion coefficients between the metal and the substrate results in lower bonding strength and weaker resistance to heat fatigue. After long-term use, the metal may peel off from the substrate, significantly increasing the risk of product failure. Additionally, metal heating inevitably produces a metallic or burnt taste. Summary of the Invention The technical objective of this application is to provide a porous ceramic atomizing core and its preparation method, aiming to solve the technical problems in related technologies where the metal heating technology route of the atomizing core is prone to oxidation and ash generation during heating, or reacts with e-liquid components to generate potentially harmful substances; it may also peel off from the substrate; and it produces a burnt taste.

[0004] To solve the above-mentioned technical problems, this application is implemented as follows.

[0005] The first aspect of this application provides a method for preparing a porous ceramic atomizing core, the method comprising: Step 1: Obtain non-conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and first solvent, wherein the weight ratio of non-conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and first solvent is (95-105):(3-45):(5-25):(12-80):(4-15):(120-300); then, after ball milling, granulation, molding, and sintering, a porous ceramic matrix is ​​obtained. Step 2: Obtain conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and second solvent, wherein the weight ratio of conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and second solvent is (50-100):(5-40):(5-35):(8-45):(5-25):(80-150); after dispersion and slurry preparation, obtain a heating slurry. Step 3: Print the heating paste prepared in step 2 onto the surface of the porous ceramic substrate prepared in step 1 to form a heating path on the porous ceramic substrate. Step 4: Sinter the porous ceramic substrate printed with heating paste to obtain a porous ceramic atomizing core.

[0006] Furthermore, in some embodiments, the diameter of the potassium hexatite whiskers is 0.2-5 μm, and / or the length of the potassium hexatite whiskers is 1-150 μm.

[0007] Furthermore, in some embodiments, the average particle size of the non-conductive ceramic powder is 5-150 μm; and / or, the average particle size of the conductive ceramic powder is 0.5-10 μm.

[0008] Furthermore, in some embodiments, the non-conductive ceramic powder includes at least one of quartz, alumina, zirconium oxide, and diatomaceous earth.

[0009] Furthermore, in some embodiments, the conductive ceramic powder includes at least one of titanium carbide, titanium nitride, titanium boride, zirconium carbide, zirconium nitride, zirconium boride, molybdenum disilicide, and titanium silicide.

[0010] Furthermore, in some embodiments, in step 3, the heating paste is printed on the surface of the porous ceramic substrate in at least one manner: line, surface, or volume.

[0011] Furthermore, in some embodiments, the sintering temperature in step 1 is 1000-1450℃; and / or, the sintering temperature in step 4 is 750~1250℃.

[0012] Furthermore, in some embodiments, the molding method in step 1 includes at least one of dry pressing, hot die casting, injection molding, and tape casting.

[0013] Further, in some embodiments, the sintering aid includes at least one of glass powder, potassium feldspar, sodium feldspar, zinc oxide, silicon oxide, and boron oxide; and / or, the binder includes at least one of polyvinyl alcohol, polyvinylpyrrolidone, acrylate emulsion, cellulose ethers, polyvinyl acetate emulsion, and sodium alginate; and / or, the pore-forming agent includes at least one of starch, sucrose, rice husk, polymethyl methacrylate, carbon black, graphite, sawdust, ammonium bicarbonate, and urea; and / or, the first solvent includes at least one of deionized water, anhydrous ethanol, acetone, and formaldehyde; and / or, the second solvent includes at least one of diethylene glycol ethyl ether acetate, butyl carbitol acetate, butyl carbitol, terpineol, paraffin wax, and oleic acid.

[0014] The second aspect of this application provides a porous ceramic atomizing core, characterized in that it is prepared by the above-described preparation method.

[0015] Compared with related technologies, the porous ceramic atomizing core and its preparation method in this application have the following advantages: This application uses conductive ceramic to replace metal as the heating path of the porous ceramic atomizing core, and adds potassium hexatite whiskers to the porous ceramic matrix and heating slurry for reinforcement, significantly improving the strength of the porous ceramic atomizing core and extending its service life. The atomizing core has strong oxidation resistance and no risk of volatiles or metal precipitation; the heating path reinforced by potassium hexatite whiskers has a high degree of matching with the thermal expansion coefficient of the matrix, significantly improving the bonding force, approaching integration, and significantly improving the resistance to thermal fatigue; it has high resistance stability, no burnt or off-flavor, and greatly improves the consistency of taste. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a schematic flowchart of the method for preparing porous ceramic atomizing core in the embodiments of this application. Detailed Implementation

[0018] The embodiments of this application are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described with reference to the accompanying drawings are exemplary and intended to explain this application, but should not be construed as limiting this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0019] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0020] Please see Figure 1 The first aspect of this application provides a method for preparing a porous ceramic atomizing core, comprising: Step 1: Obtain non-conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and first solvent, wherein the weight ratio of non-conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and first solvent is (95-105):(3-45):(5-25):(12-80):(4-15):(120-300); then, after ball milling, granulation, molding, and sintering, a porous ceramic matrix is ​​obtained. Step 2: Obtain conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and second solvent, wherein the weight ratio of conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and second solvent is (50-100):(5-40):(5-35):(8-45):(5-25):(80-150); after dispersion and slurry preparation, obtain a heating slurry. Step 3: Print the heating paste prepared in step 2 onto the surface of the porous ceramic substrate prepared in step 1 to form a heating path on the porous ceramic substrate. Step 4: Sinter the porous ceramic substrate printed with heating paste to obtain a porous ceramic atomizing core.

[0021] In this embodiment, the conductive circuit formed by using conductive ceramic instead of metal has advantages such as oxidation resistance, high temperature resistance, and no ash content. It eliminates the risks of burn-out and carbon buildup, and its health and safety level and service life are far superior to those of metal materials. Furthermore, the conductive ceramic heating path eliminates the risk of metal precipitation and pollution, exhibits high chemical stability, does not react with e-liquid components, is more inert to flavorings, acids, and alkalis, maintains long-term stable resistance, and produces odorless vaporization and a purer vaping experience. Compared to the risk of peeling from the substrate due to the larger coefficient of thermal expansion of metal materials, the thermal expansion coefficient of the conductive ceramic heating path is closer to that of the porous ceramic matrix, resulting in higher bonding strength and making it less prone to detachment or peeling at high temperatures.

[0022] In addition, in the embodiments of this application, an appropriate amount of potassium hexatitanate (K2Ti6O) is added to the porous ceramic matrix. 13Whiskers can form a three-dimensional network structure within a ceramic matrix, achieving strengthening and toughening through bridging, pull-out, and crack deflection. This significantly improves the flexural, compressive, and thermal shock resistance of porous ceramic matrices, making them less prone to cracking and breakage, and significantly extending their service life. Simultaneously, potassium hexatite whiskers possess a tunnel-like crystal structure, K... + Embedded within the titanium-oxygen framework tunnels, potassium hexatite whiskers can construct continuous, interconnected, and uniform microporous channels within the porous ceramic matrix. This allows for adjustable pore size and porosity, preventing pore closure, blockage, and localized dry burning. The liquid delivery speed is stable and controllable, resulting in fine atomization and consistent flavor. Furthermore, potassium hexatite whiskers are resistant to acids and alkalis, and resistant to e-liquid corrosion. They do not react with smoke or e-liquid at high temperatures, and produce no heavy metals or odors, meeting the safety and pure flavor requirements of the atomizer core. Additionally, the addition of potassium hexatite whiskers results in less deformation and lower shrinkage after sintering of the porous ceramic matrix, facilitating precision molding and mass production, thus improving product consistency and yield. Moreover, potassium hexatite whiskers offer excellent thermal insulation; therefore, adding them to the porous ceramic matrix significantly reduces heat loss, concentrates heat generation, improves electrothermal conversion efficiency, and lowers the temperature of the e-cigarette casing, enhancing safety.

[0023] Furthermore, this application incorporates potassium hexatite whiskers into the conductive ceramic for the heating path. This creates a mechanical anchoring and bridging between the heating path and the porous ceramic matrix, significantly improving the interfacial bonding strength and resolving the issues of easy detachment, cracking, and failure of the heating path after repeated high-temperature heating. Moreover, potassium hexatite whiskers have microcrack bridging and toughening effects, absorbing thermal stress and inhibiting cracking, warping, and localized burn-out of the conductive ceramic heating path during thermal cycling, thus extending the lifespan of the heating path several times over. The potassium hexatite whiskers form a uniform network within the conductive ceramic heating path, reducing current concentration and hotspot effects, resulting in a more uniform temperature distribution. This further prevents localized high temperatures from causing e-liquid decomposition and a burnt taste, improving flavor consistency. The low coefficient of thermal expansion of potassium hexatite whiskers is highly compatible with the porous ceramic matrix, reducing thermal mismatch stress between the conductive ceramic heating path and the matrix, preventing brittleness and failure under frequent heating and cooling conditions. Potassium hexatite whiskers, being an insulating phase, allow for precise adjustment of the conductive path in the heating path of conductive ceramics, resulting in stable and consistent resistivity. This enables accurate temperature control within the 250–400℃ range with minimal resistance fluctuations. Potassium hexatite whiskers also improve the rheological properties of conductive ceramic pastes, leading to smoother printing and coating processes, uniform film thickness, and the absence of pinholes and sagging, significantly enhancing the yield and consistency of the atomizing core heating path.

[0024] Understandably, the heating path can refer to the heating circuit and / or heating film.

[0025] In some embodiments, for step 1 and / or step 2, the diameter of the potassium hexatite whisker is 0.2-5 μm, and / or the length of the potassium hexatite whisker is 1-150 μm.

[0026] Specifically, the diameter of potassium hexatite whiskers can be 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 μm, etc., and / or the length of potassium hexatite whiskers can be 1, 50, 100, 150 μm, etc. By limiting the diameter and / or length of potassium hexatite whiskers, they can better form a three-dimensional network structure within the porous ceramic matrix, which is more conducive to improving the toughness of the porous ceramic matrix. Simultaneously, it allows for better adjustment of the pore size and porosity of the porous ceramic matrix. Furthermore, the heating path can achieve better connection with the porous ceramic, improving the interfacial strength, and the heating path is less likely to detach from the porous ceramic matrix at high temperatures.

[0027] In some embodiments, for step 1 and / or step 2, the average particle size of the non-conductive ceramic powder is 5-150 μm; and / or, the average particle size of the conductive ceramic powder is 0.5-10 μm.

[0028] Specifically, non-conductive ceramic powder is used in porous ceramic matrices, which require a certain structural strength. Therefore, the average particle size of non-conductive ceramic powder can be 5, 50, 100, 150 μm, etc. On the other hand, conductive ceramic powder is used in heating pastes. Therefore, conductive ceramic powder needs to be fine with a small particle size, which can be 0.5, 2, 5, 7, 10 μm, etc.

[0029] In some embodiments, for step 1, the non-conductive ceramic powder includes at least one of quartz, alumina, zirconium oxide, and diatomaceous earth. Potassium hexatitanate whiskers have good compatibility with quartz, alumina, zirconium oxide, diatomaceous earth, etc., which is beneficial for forming a structurally stable porous ceramic matrix.

[0030] In some embodiments, for step 2, the conductive ceramic powder includes at least one of titanium carbide, titanium nitride, titanium boride, zirconium carbide, zirconium nitride, zirconium boride, molybdenum disilicide, and titanium silicide. It is conductive and combines the high hardness, oxidation resistance, and chemical inertness of ceramics with the low resistivity and conductivity of metals. Its crystal structure arrangement is similar to that of graphite, and it has excess free electrons, thus exhibiting a metal-like electronic conductivity. It can be used as a heating paste and can be adapted to the thermal expansion coefficient of porous ceramic matrices, resulting in higher bonding strength and resistance to detachment at high temperatures.

[0031] Furthermore, in some embodiments, in step 3, the heating paste is printed on the surface of the porous ceramic substrate in at least one manner: line, surface, or volume.

[0032] Specifically, the heating mode of the heating path can be diverse and adjustable, not only linear heating but also surface heating and / or volume heating. This allows for adjustment of the heating mode based on the porous ceramic substrate and actual heating conditions, preventing localized overheating and core clogging. Understandably, the surface of a porous ceramic substrate can include both linear and surface heating. This application does not limit the shape of the heating path on the porous ceramic substrate. For example, it can be S-shaped, U-shaped, Z-shaped, etc.

[0033] Furthermore, in some embodiments, the sintering temperature in step 1 is 1000-1450°C.

[0034] Specifically, the sintering temperature in step 1 can be 1000, 1100, 1200, 1300, 1400, 1450℃, etc. Adding an appropriate amount of potassium hexatitanate whiskers to the porous ceramic matrix provides high-temperature stability. In addition, in some embodiments, the temperature can be maintained for 0.5-3 hours after sintering.

[0035] In some embodiments, the sintering temperature in step 4 is 750~1250℃. Specifically, the sintering temperature in step 4 can be 750, 800, 900, 1000, 1100, 1200, 1250℃, etc. Because the heating paste is made of conductive ceramic, the bonding strength between the heating path and the porous ceramic matrix is ​​higher, and the heating paste is not easy to peel off at high temperatures. In addition, the heating path reinforced by potassium hexatate whiskers has a higher coefficient of thermal expansion matching with the porous ceramic matrix and the bonding force is significantly improved, which can significantly improve the heat resistance.

[0036] Furthermore, in some embodiments, the forming method in step 1 includes at least one of dry pressing, hot die casting, injection molding, and tape casting. Potassium hexatite whiskers have good compatibility with the matrix material and are suitable for forming processes such as dry pressing, hot die casting, injection molding, and tape casting.

[0037] In some embodiments, the sintering aid includes at least one selected from glass powder, potassium feldspar, sodium feldspar, zinc oxide, silicon oxide, and boron oxide. Both steps 1 and 4 require a sintering process, and adding sintering aids facilitates this process.

[0038] In some embodiments, the binder includes at least one selected from polyvinyl alcohol, polyvinylpyrrolidone, acrylate emulsion, cellulose ether, polyvinyl acetate emulsion, and sodium alginate. The binder facilitates tighter bonding of various powders and promotes molding.

[0039] In some embodiments, the pore-forming agent includes at least one selected from starch, sucrose, rice husk, polymethyl methacrylate, carbon black, graphite, sawdust, ammonium bicarbonate, and urea. The pore-forming agent can form porous ceramics, which can be used for storing and transporting atomizing media in the atomizing core.

[0040] In some embodiments, the first solvent includes at least one selected from deionized water, anhydrous ethanol, acetone, and formaldehyde. The first solvent can be deionized water or an organic solvent.

[0041] In some embodiments, the second solvent includes at least one selected from diethylene glycol ethyl ether acetate, butyl carbitol acetate, butyl carbitol, terpineol, paraffin, and oleic acid. The second solvent may be an organic solvent.

[0042] The second aspect of this application provides a porous ceramic atomizing core, which is prepared by the above-described method.

[0043] This application employs conductive ceramics instead of metals as the heating path for the porous ceramic atomizing core, and adds potassium hexatite whiskers to the porous ceramic matrix and heating paste for reinforcement. This significantly improves the strength of the porous ceramic atomizing core and extends its service life. The atomizing core has strong oxidation resistance and no risk of volatiles or metal precipitation; the heating path reinforced by potassium hexatite whiskers has a high degree of matching with the thermal expansion coefficient of the matrix, significantly improving the bonding force and approaching integration, thus significantly improving the resistance to thermal fatigue; it also has high resistance stability, no burnt or off-flavors, and greatly improves the consistency of taste.

[0044] The present application is further illustrated below with specific embodiments.

[0045] Example 1 Step 1: Formula weighing: According to the mass ratio, weigh 80 parts quartz, 20 parts diatomaceous earth powder, 10 parts glass powder, 6 parts albite, and 25 parts starch separately, with a total powder weight of 5 kg; separately weigh 10 parts potassium hexatitanate whiskers and 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.2. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder, whiskers and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve, then perform centrifugal spray granulation, sieve the granulated powder, and take the granulated powder between 80 and 120 mesh for compaction and use. Step 5: Pressing: The pressing process of granulated powder is as follows: the forming pressure is 35MPa and the holding time is 5s. The green body size is 7.5mm in length, 5.5mm in width and 2.5mm in thickness. The green body is then dried at 80℃ for 8 hours. Step 6: High-temperature sintering: The sintering process involves holding at 1055℃ for 2.5 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 100 parts of titanium nitride powder, 8 parts of potassium hexatitanate whiskers, 6 parts of glass powder, 4 parts of sodium feldspar, 8 parts of cellulose ethers, 15 parts of starch, and 85 parts of anhydrous ethanol respectively, and pour them into the container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry. Step 8: Printing pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm and the heating path is arc-shaped. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 960℃ for 2 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0046] Example 2 Step 1: Formula weighing: According to the mass ratio, weigh 80 parts quartz, 20 parts diatomaceous earth powder, 10 parts glass powder, 6 parts albite, and 25 parts starch separately, with a total powder weight of 5 kg; separately weigh 10 parts potassium hexatitanate whiskers and 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.2. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder, whiskers and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve, then perform centrifugal spray granulation, sieve the granulated powder, and take the granulated powder between 80 and 120 mesh for compaction and use. Step 5: Pressing: The pressing process of granulated powder is as follows: the forming pressure is 35MPa and the holding time is 5s. The green body size is 7.5mm in length, 5.5mm in width and 2.5mm in thickness. The green body is then dried at 80℃ for 8 hours. Step 6: High-temperature sintering: The sintering process involves holding at 1055℃ for 2.5 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 100 parts of titanium nitride powder, 8 parts of potassium hexatitanate whiskers, 6 parts of glass powder, 4 parts of sodium feldspar, 8 parts of cellulose ethers, 15 parts of starch, and 85 parts of anhydrous ethanol respectively, and pour them into the container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry. Step 8: Printing pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm, the heating path is a rectangular surface with a size of 6mm*4mm. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 960℃ for 2 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0047] Example 3 Step 1: Formula weighing: According to the mass ratio, weigh 80 parts quartz, 20 parts diatomaceous earth powder, 10 parts glass powder, 6 parts albite, and 25 parts starch separately, with a total powder weight of 5 kg; separately weigh 10 parts potassium hexatitanate whiskers and 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.2. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder, whiskers and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve, then perform centrifugal spray granulation, sieve the granulated powder, and take the granulated powder between 80 and 120 mesh for compaction and use. Step 5: Pressing: The pressing process of granulated powder is as follows: the forming pressure is 35MPa and the holding time is 5s. The green body size is 7.5mm in length, 5.5mm in width and 2.5mm in thickness. The green body is then dried at 80℃ for 8 hours. Step 6: High-temperature sintering: The sintering process involves holding at 1055℃ for 2.5 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 100 parts of titanium nitride powder, 8 parts of potassium hexatitanate whiskers, 6 parts of glass powder, 4 parts of sodium feldspar, 8 parts of cellulose ethers, 15 parts of starch, and 85 parts of anhydrous ethanol respectively, and pour them into the container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry. Step 8: Printing Pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm, and the heating path is rectangular. That is, conductive ceramic paste is printed on all four sides of the porous ceramic in the thickness direction. The two sides with the smallest symmetrical area are selected as electrodes, and the two sides with the largest area are selected as heating paths to form a parallel heating circuit, which drives the whole to heat up. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 960℃ for 2 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0048] Example 4 Step 1: Formula weighing: According to the mass ratio, weigh 80 parts quartz, 20 parts diatomaceous earth powder, 10 parts glass powder, 6 parts albite, and 25 parts starch separately, with a total powder weight of 5 kg; separately weigh 18 parts potassium hexatitanate whiskers and 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.2. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder, whiskers and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve, then perform centrifugal spray granulation, sieve the granulated powder, and take the granulated powder between 80 and 120 mesh for compaction and use. Step 5: Pressing: The pressing process of granulated powder is as follows: the forming pressure is 35MPa and the holding time is 5s. The green body size is 7.5mm in length, 5.5mm in width and 2.5mm in thickness. The green body is then dried at 80℃ for 8 hours. Step 6: High-temperature sintering: The sintering process involves holding at 1055℃ for 2.5 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 100 parts of titanium nitride powder, 11 parts of potassium hexatitanate whiskers, 8 parts of glass powder, 6 parts of sodium feldspar, 8 parts of cellulose ethers, 15 parts of starch, and 85 parts of anhydrous ethanol respectively, and pour them into the container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry. Step 8: Printing pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm and the heating path is arc-shaped. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 960℃ for 2 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0049] Example 5 Step 1: Formula weighing: According to the mass ratio, weigh 80 parts quartz, 20 parts diatomaceous earth powder, 10 parts glass powder, 6 parts albite, and 35 parts starch separately, with a total powder weight of 5 kg; separately weigh 10 parts potassium hexatitanate whiskers and 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.2. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder, whiskers and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve, then perform centrifugal spray granulation, sieve the granulated powder, and take the granulated powder between 80 and 120 mesh for compaction and use. Step 5: Pressing: The pressing process of granulated powder is as follows: the forming pressure is 35MPa and the holding time is 5s. The green body size is 7.5mm in length, 5.5mm in width and 2.5mm in thickness. The green body is then dried at 80℃ for 8 hours. Step 6: High-temperature sintering: The sintering process involves holding at 1055℃ for 2.5 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 100 parts of titanium nitride powder, 11 parts of potassium hexatitanate whiskers, 8 parts of glass powder, 6 parts of sodium feldspar, 8 parts of cellulose ethers, 15 parts of starch, and 85 parts of anhydrous ethanol respectively, and pour them into the container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry. Step 8: Printing pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm and the heating path is arc-shaped. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 960℃ for 2 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0050] Example 6 Step 1: Formula weighing: According to the mass ratio, weigh 70 parts quartz, 10 parts alumina powder, 20 parts diatomaceous earth powder, 12 parts boron oxide powder, 8 parts albite, and 20 parts graphite separately, with a total powder weight of 5 kg; separately weigh 20 parts potassium hexatitanate whiskers and 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.5. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder, whiskers and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve. Then, perform centrifugal spray granulation. Heat and stir the granulated powder with paraffin and oleic acid at a mass ratio of 10:4:1 to prepare the preparative material. Step 5: Hot pressing: The prepared material is put into the hot pressing chamber. The hot pressing process is as follows: molding pressure 5MPa, holding time 3s, molding temperature 65℃, green blank size 7.5mm long, 5.5mm wide, and 2.5mm thick. Step 6: High-temperature sintering: The sintering process involves holding at 1075℃ for 3.0 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 70 parts of titanium carbide powder, 30 parts of titanium boride powder, 15 parts of potassium hexatitanate whiskers, 10 parts of glass powder, 4 parts of sodium feldspar, 8 parts of polyvinylpyrrolidone, 10 parts of graphite, and 100 parts of terpineol, and pour them into a container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry; Step 8: Printing pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm and the heating path is arc-shaped. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 1010℃ for 2.5 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0051] In addition, this application provides two comparative examples.

[0052] Comparative Example 1 Step 1: Weighing the formula: According to the mass ratio, weigh 80 parts quartz, 20 parts diatomaceous earth powder, 10 parts glass powder, 6 parts albite, and 25 parts starch separately, with a total powder weight of 5 kg; separately weigh 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.2. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve, then perform centrifugal spray granulation, sieve the granulated powder, and take the granulated powder between 80 and 120 mesh for compaction and use. Step 5: Pressing: The pressing process of granulated powder is as follows: the forming pressure is 35MPa and the holding time is 5s. The green body size is 7.5mm in length, 5.5mm in width and 2.5mm in thickness. The green body is then dried at 80℃ for 8 hours. Step 6: High-temperature sintering: The sintering process involves holding at 1055℃ for 2.5 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 100 parts of iron-chromium alloy powder, 6 parts of glass powder, 4 parts of sodium feldspar, 8 parts of cellulose ether, and 85 parts of anhydrous ethanol respectively, and pour them into the container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry. Step 8: Printing pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm and the heating path is arc-shaped. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 960℃ for 2 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0053] Comparative Example 2 Step 1: Weighing the formula: According to the mass ratio, weigh 80 parts quartz, 20 parts diatomaceous earth powder, 10 parts glass powder, 6 parts albite, and 25 parts starch separately, with a total powder weight of 5 kg; separately weigh 15 parts polyvinyl alcohol. Step 2: Weigh out the alumina grinding balls and deionized water according to the mass ratio of balls:powder:deionized water of 3:1:1.2. Step 3: Mixing and ball milling: First, pour deionized water and polyvinyl alcohol into the ball mill bucket, then pour in the powder and grinding balls, close the lid and place it in the ball mill. Ball milling process: speed 70 rpm, time 10 hours; Step 4: Granulation: Take out the ball mill slurry and pass it through a 150-mesh sieve, then perform centrifugal spray granulation, sieve the granulated powder, and take the granulated powder between 80 and 120 mesh for compaction and use. Step 5: Pressing: The pressing process of granulated powder is as follows: the forming pressure is 35MPa and the holding time is 5s. The green body size is 7.5mm in length, 5.5mm in width and 2.5mm in thickness. The green body is then dried at 80℃ for 8 hours. Step 6: High-temperature sintering: The sintering process involves holding at 1055℃ for 2.5 hours. Step 7: Preparation of heating slurry: According to the mass ratio, weigh 100 parts of iron-chromium alloy powder, 6 parts of glass powder, 4 parts of sodium feldspar, 8 parts of cellulose ether, and 85 parts of anhydrous ethanol respectively, and pour them into the container of a high-speed mixer for high-speed centrifugal dispersion to prepare a thick slurry. Step 8: Printing pattern: The sintered porous ceramic blank is fixed in a specific fixture and transferred to the designated area of ​​the screen printing machine. The heating paste is printed on the surface of the porous ceramic by the screen printing machine. The paste thickness is 100μm, the heating path is a rectangular surface with a size of 6mm*4mm. Step 9: Secondary sintering: The porous ceramic with the printed paste is placed in a sintering furnace for secondary sintering at a temperature of 960℃ for 2 hours to obtain the porous ceramic atomizing core. Step 10: Performance testing of the porous ceramic atomizing core.

[0054] Furthermore, in this application, performance tests were conducted on the porous ceramic atomizing cores obtained in each embodiment and comparative example. Specific test methods included: Porosity: Refer to the test method for apparent porosity in GB / T 25995-2010.

[0055] Average pore size: Tested in accordance with GB / T 1967-1996.

[0056] Pore ​​structure morphology: Tested according to the mercury porosimetry method in GB / T 21650.1-2008.

[0057] Bending strength: Tested in accordance with GB / T 1965-2023.

[0058] Compressive strength: Tested in accordance with GB / T 1964-2023.

[0059] Heating response speed: With an infrared thermometer pointed at the fixed point of the heating surface of the atomizing core, the two electrodes are connected to the power supply. By turning on the power, timing, and measuring the temperature, the corresponding heating response speed can be calculated.

[0060] Atomization volume: Using a uniform mint-flavored e-liquid, the device is installed and tested on professional equipment to simulate human inhalation. The heating power and heating response speed test power are consistent, allowing for a direct observation of the amount of vapor produced with each puff.

[0061] Aroma / Flavor: The device was equipped with a uniform mint-flavored e-liquid, and the heating power and heating response speed were tested using the same power. The same person conducted the vaping and provided feedback.

[0062] Carbon buildup on the atomizer core: The device was installed using a uniform mint-flavored e-liquid. Professional equipment was used to replace human vaping. The heating power and heating response speed were the same as those used for testing. Continuous vaping was performed until 5ml of e-liquid was used up. The device was then disassembled to observe the surface condition of the atomizer core.

[0063] Resistance stability: Before installing the atomizer core, the initial resistance value is measured with a professional testing instrument. Then, a uniform mint-flavored e-liquid is used for installation. A professional device is used to replace the human vaping action. The heating power and the power used for heating response speed testing are the same. Continuous vaping is performed until the e-liquid is exhausted. The prototype is then disassembled, and the resistance value is measured again. The difference between the resistance values ​​before and after measurement can be used to calculate the resistance value change rate.

[0064] The test results for Comparative Examples 1 and 2 and Examples 1 and 2 are shown in the table below:

[0065] (Continued)

[0066] The test results of Examples 3 to 6 are shown in the table below:

[0067] (Continued)

[0068] The test results above show that the heating path material of Comparative Example 1 is a commonly used iron-chromium alloy, and the circuit is a common bow-shaped design. The overall performance of the atomizer core exhibits the common problems of porous ceramic atomizer cores currently on the market, namely low strength, metallic taste, poor experience, easy carbon buildup, and short lifespan. This is mainly caused by the low strength of the porous ceramic matrix itself and the metal heating path. During the heating process, the metal oxidizes and produces ash, resulting in a metallic taste. Secondly, the porous ceramic has many closed and irregular pores, which will affect the e-liquid supply capacity with continuous vaping, and easily produce a burnt taste during e-liquid atomization. In this process, the metal is prone to overheating and heat accumulation, inevitably leading to carbon buildup. In addition, the thermal expansion coefficient of the metal circuit differs greatly from that of the ceramic matrix, resulting in poor matching. With the increase of vaping times, the presence of thermal fatigue stress at the junction of the metal and ceramic will cause defects inside the metal, which will not only cause a significant change in resistance but also increase the risk of detachment, thus reducing the service life. Comparative Example 2 is based on Comparative Example 1, except that the heating path is changed to surface heating. The test results show that the overall performance of the surface heating atomizer is significantly weaker than that of Comparative Example 1. This is mainly because the surface heating mode of the metal material has low resistance and no heating burst force, so it cannot fully atomize the e-liquid.

[0069] Example 1, based on Comparative Example 1, adds a certain proportion of potassium hexatitanate whiskers to the porous ceramic matrix, and changes the heating path from metal to conductive ceramic. The strength of the porous ceramic in Example 1 is significantly improved compared to Comparative Example 1, mainly due to the significant toughening and reinforcing function of potassium hexatitanate whiskers. The heating response speed of the atomizer core can reach a higher temperature in a shorter time, which is a significant advantage of conductive ceramics. Secondly, the vapor volume is also significantly increased, resulting in a better experience, no metallic taste, a rich and stable aroma, no carbon buildup in the atomizer core, and higher stability. The above data shows that conductive ceramics have significant iterative advantages over metal as a heating path. In addition, adding potassium hexatitanate whiskers to the heating path also helps to improve the heating and atomization effect, making the thermal expansion coefficient of the heating path and the matrix more compatible, thus helping to improve the vaping experience of the atomizer core and extend its service life.

[0070] Example 2, based on Example 1, upgrades the heating path of the conductive ceramic from an arc-shaped pattern to surface heating, further improving the overall performance of the atomizing core. Due to the increased heating area, the area covered by potassium hexatite whiskers also increases, positively impacting the strength of the atomizing core. Furthermore, resistance stability is further improved, significantly extending service life. The performance data of Example 2 contrasts sharply with Comparative Example 2, fully highlighting the advantages of the combined performance of conductive ceramic and potassium hexatite whiskers.

[0071] Example 3, based on Example 2, upgrades the conductive ceramic heating path to a rectangular shape, further expanding the heating surface and improving the overall performance of the atomizing core. A comprehensive data comparison of Examples 1-3 with Comparative Examples 1 and 2 further demonstrates that the conductive circuit formed by conductive ceramics instead of metal has advantages such as oxidation resistance, high temperature resistance, and no ash content. It eliminates the risk of burnout and carbon buildup, and its health and safety level and service life are far superior to metal materials. The resistivity of conductive ceramics is more adjustable; the heating path can not only provide linear heating but also surface and volume heating, avoiding localized hot spots and core clogging. The conductive ceramic heating path eliminates the risk of metal precipitation and pollution, has high chemical stability and does not react with e-liquid components, is more inert to flavorings, acids, and alkalis, and maintains long-term stable resistance, resulting in odorless atomization and a purer inhalation experience. Potassium hexatite whiskers can form a three-dimensional network structure within the ceramic, achieving toughness through bridging, pull-out, and crack deflection, significantly improving the porous ceramic's resistance to bending, compression, and thermal shock, making it less prone to cracking and breakage, and significantly extending its service life. Whiskers can construct continuous, interconnected, and uniform microporous channels with adjustable pore size and porosity, avoiding closed pores, blockage, and localized dry burning. The liquid conduction speed is stable and controllable, resulting in fine atomization and consistent taste. Whiskers themselves have low thermal conductivity and good thermal insulation, which can significantly reduce heat loss, make heat generation more concentrated, and improve electrothermal conversion efficiency.

[0072] Example 4, based on Example 1, increased the content of potassium hexatitanate whiskers in the matrix and heating path, further enhancing the strength of the porous ceramic. Due to the low thermal conductivity of potassium hexatitanate whiskers and the advantages of optimized pore structure, the heating response speed of the atomizer core is faster, further improving the atomized flavor. Example 5, based on Example 1, increased the porosity of the porous ceramic. The increase in porosity did not significantly reduce the strength of the atomizer core, remaining higher than that of Comparative Example 1. Moreover, the increased porosity did not reduce the atomization experience; the overall inhalation feedback was close to that of Example 4. The porous ceramic in Example 6 employed a hot-pressing process. The overall performance of the atomizer core remained stable, similar to Examples 1 and 2. Compared to dry pressing, hot-pressing has the advantages of simpler equipment, lower investment, and the ability to mass-produce, further reducing production costs.

[0073] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.

[0074] The above is a description of the technical solutions provided in this application. For those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the embodiments of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A method for preparing a porous ceramic atomizing core, characterized in that, The preparation method includes: Step 1: Obtain non-conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and first solvent, wherein the weight ratio of non-conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and first solvent is (95-105):(3-45):(5-25):(12-80):(4-15):(120-300); then, after ball milling, granulation, molding, and sintering, a porous ceramic matrix is ​​obtained. Step 2: Obtain conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and second solvent, wherein the weight ratio of conductive ceramic powder, potassium hexatitanate whiskers, sintering aid, pore-forming agent, binder, and second solvent is (50-100):(5-40):(5-35):(8-45):(5-25):(80-150); after dispersion and slurry preparation, obtain a heating slurry. Step 3: Print the heating paste prepared in step 2 onto the surface of the porous ceramic substrate prepared in step 1 to form a heating path on the porous ceramic substrate. Step 4: Sinter the porous ceramic substrate printed with heating paste to obtain a porous ceramic atomizing core.

2. The preparation method according to claim 1, characterized in that, The potassium hexatite whiskers have a diameter of 0.2-5 μm and / or a length of 1-150 μm.

3. The preparation method according to claim 1, characterized in that, The average particle size of the non-conductive ceramic powder is 5-150 μm; and / or, the average particle size of the conductive ceramic powder is 0.5-10 μm.

4. The preparation method according to claim 3, characterized in that, The non-conductive ceramic powder includes at least one of quartz, alumina, zirconium oxide, and diatomaceous earth.

5. The preparation method according to claim 3, characterized in that, The conductive ceramic powder includes at least one of titanium carbide, titanium nitride, titanium boride, zirconium carbide, zirconium nitride, zirconium boride, molybdenum disilicide, and titanium silicide.

6. The preparation method according to claim 1, characterized in that, In step 3, the heating paste is printed on the surface of the porous ceramic substrate in at least one of the following ways: line, surface, or volume.

7. The preparation method according to claim 1, characterized in that, The sintering temperature in step 1 is 1000-1450℃; And / or, the sintering temperature in step 4 is 750~1250℃.

8. The preparation method according to claim 1, characterized in that, The molding method in step 1 includes at least one of dry pressing, hot die casting, injection molding, and tape casting.

9. The preparation method according to claim 1, characterized in that, The sintering aid includes at least one of glass powder, potassium feldspar, sodium feldspar, zinc oxide, silicon oxide, and boron oxide; And / or, the adhesive comprises at least one of polyvinyl alcohol, polyvinylpyrrolidone, acrylate emulsion, cellulose ether, polyvinyl acetate emulsion, and sodium alginate; And / or, the pore-forming agent includes at least one of starch, sucrose, rice husk, polymethyl methacrylate, carbon black, graphite, sawdust, ammonium bicarbonate, and urea; And / or, the first solvent includes at least one of deionized water, anhydrous ethanol, acetone, and formaldehyde; And / or, the second solvent includes at least one of diethylene glycol ethyl ether acetate, butyl carbitol acetate, butyl carbitol, terpineol, paraffin, and oleic acid.

10. A porous ceramic atomizing core, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.